1988
DOI: 10.1111/j.1399-3054.1988.tb09202.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐volume curves and drought resistance in two wheat genotypes

Abstract: The water relations of two durum wheat cultivars (Triticum durum Desf.) were studied throughout the growing season. Irrigated and unirrigated plants were compared from booting to milk stage; a period where water stress occurred naturally in the field. Modulus of elasticity (ε), turgid weight/dry weight ratio (TW/DW), relative water content at zero turgor (RWCo) and osmotic potential at full turgor (ε) declined throughout the season while average turgor (ψp) increased. Water stress induced a further decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Highest root/ shoot ratio was observed in the seedlings when Cr +6 -EDDHA (10µM) was supplemented in the nutrient solutions. Fresh and dry mass though decreased with increase in chromium concentrations exhibited a modulatory role as reported elsewhere [20]. Total chlorophyll content in the seedlings treated with Cr +6 -EDTA (10µM) solution was more as compared to other treatments Fig.…”
Section: Results and Discussion Growth Parameter Studysupporting
confidence: 52%
“…Highest root/ shoot ratio was observed in the seedlings when Cr +6 -EDDHA (10µM) was supplemented in the nutrient solutions. Fresh and dry mass though decreased with increase in chromium concentrations exhibited a modulatory role as reported elsewhere [20]. Total chlorophyll content in the seedlings treated with Cr +6 -EDTA (10µM) solution was more as compared to other treatments Fig.…”
Section: Results and Discussion Growth Parameter Studysupporting
confidence: 52%
“…5). A positive relationship between cell-wall rigidity and S value has also been found by other authors (Cutler et al 1977;Düring 1986;Rascio et al 1988;Kubiske and Abrams 1991;Wan et al 1993;Fan et al 1994). The capacity to maintain an adequate amount of water in the cell at low water potential could be an adaptive characteristic in species which experience moderate water stress (e.g.…”
Section: Tablementioning
confidence: 52%
“…Differential enthalpy (AH) was calculated through van't Hoff analysis of adsorption isotherms at 5 and 20°C, which allowed us to determine the strength of water binding. AH Several studies have shown that in leaves of plants exposed to water stress the increase in osmotic pressure is associated with a decrease in T/D2 (8,11,16,21). Changes in water content and accumulation of osmotically active and inactive dry matter would lead to a reduction in T/D ratio (16).…”
mentioning
confidence: 99%